'Distinctiveness' and the BBC: a new battleground for public service television?. (October 2017) - Goddard, Peter
UK government-led consultations over the renewal of the BBC's Charter, and the new 2017 Charter itself, have foregrounded the 'distinctiveness' of the BBC's output, especially in popular entertainment television. Focusing on these debates and proposals, this article considers the value of distinctiveness when applied to BBC television, identifying definitions of the term and its history (or lack of it) in previous debates about the British broadcasting system. It discusses the implications of proposed systems for measuring distinctiveness quantitatively. It examines why the publicly funded, not-for-profit model of broadcasting might be expected to yield more distinctive outputs, yet also detects the spectre of concerns about the BBC's market impact to be present in the background of these debates, in relation both to the production of entertainment content and to its scheduling. The article argues that the domestic and global economic and cultural benefits arising from the BBC's potential for creating 'distinctive' programming should outweigh concerns about market impact. It also concludes that 'distinctiveness' adds little to the BBC's existing service requirements, but risks being used prescriptively and as a weapon with which the BBC's output can constantly be questioned by its critics.